Dari Malang Raya Menuju Iman yang Hidup: Isu Feminisme dan Teologi Kontekstual - Snae, Yeremias Benediktus Sae (Aditya Wacana Pusat Pengkajian Agama Dan Kebudayaan, 2015)
The article argues that faith speaks aloud only when it involves deeply into every human experience. Faith does not come out of nor descends from heaven. It exists precisely within human life. Only when it speaks in the language and logic of the people, it produces a lot of fruits. With this consideration the writer tries to reflect theologically issues on feminism as they are reported in the daily Jawa Pos newspaper, particularly in its three Radars, namely Radar Malang, Radar Kanjuruhan, and Radar Batu during the period of August and September 2015. He, then, found out the face of the Greater Malang as charming and beautiful, reflecting Ken Dedes (13th century), the pretty and superior Queen of Singhasari Kingdom, mother of the kings of Java. As the Greater Malang is naturally beautiful and alluring as the Queen Ken Dedes so does faith of Christianity. The local Church is called to live out the faith in accordance with the charming nature of Malang and to present herself in a motherly way for all.